Memposisikan Pustakawan di Perpustakaan Daerah dalam Pengembangan E- Government - Prakoso, Bambang (Universitas Wijaya Kusuma Surabaya, 2019)
Regional libraries have a fundamental role in changing regional civilizations, Librarians become an important slice in realizing the role to be optimally active, in various library activities that have undergone various changes caused by the development of science and technology, really need adequate readiness to be able to meet community expectations. The development of e-government as one method to be able to maximize government business efficiency and can streamline the section relating to the service channel to the public, information dissemination is very fast and even, can reduce the cost of printing (publishing) by making an electronic version of the documents available, so it is possible to make cost savings. As for one of the many ways done is by building a website or government site on the Internet. Librarians who work in regional libraries are expected to be adaptive to the development of information technology to provide maximum service to users of regional libraries.